Lovely little embroideries : 19 dimensional flower bouquet designs for hand stitching - Stackhouse, Beth (Landauer Publishing, an imprint of Fox Chapel Publishing, 2022)
"The author presents chapters on embroidery basics and techniques, including an illustrated stitch guide detailing all of the stitches used in the included projects, plus step-by-step instructions and illustrations for 19 small hoop designs"--